2017
DOI: 10.26773/mjssm.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Awareness of the Links between Physical Activity and Health

Abstract: Th e eff ectiveness of physicians in providing advice to patients about physical activity (PA) is infl uenced by their own understanding of the links between PA and health, as well as by their own PA habits. Th is study involved pre-clinical medical students in New Zealand, examining their baseline knowledge, skills, and attitudes towards advising patients about PA, as well as eliciting their personal exercise habits. A total of 234 students (age 20.9±2.9 years; 46% males; participation rate: 99%) completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
2
20
1
1
Order By: Relevance
“…PA also has intrinsic benefits for students in terms of their own health and wellbeing (Dyrbye, Satele & Shanafelt, 2016). The authors of this paper recently reported that third year (pre-clinical) medical students in New Zealand were generally physically active and had a good understanding of the links between PA and health, but were lacking skills for PA advising and knowledge of specific PA guidelines for healthy individuals and clinical populations (Mandic, Wilson, Clark-Grill & O'Neill, 2017). In addition, regularly active medical students felt more confident in providing PA advice and perceived a greater impact of PA advising on patients' quality of life (Mandic et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…PA also has intrinsic benefits for students in terms of their own health and wellbeing (Dyrbye, Satele & Shanafelt, 2016). The authors of this paper recently reported that third year (pre-clinical) medical students in New Zealand were generally physically active and had a good understanding of the links between PA and health, but were lacking skills for PA advising and knowledge of specific PA guidelines for healthy individuals and clinical populations (Mandic, Wilson, Clark-Grill & O'Neill, 2017). In addition, regularly active medical students felt more confident in providing PA advice and perceived a greater impact of PA advising on patients' quality of life (Mandic et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Outcome measures and measurement procedures have been described in detail elsewhere (Mandic et al, 2017) and are briefly summarized below.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Školska unakrsna studija" (Novak, Milanovic, Radisavljevic Janic, Stefan & Kristicevic, 2016), "Poznavanje nauke o fitnesu kod srednjoškolaca u javnim i privatnim školama" (Serbes, Cengiz, Sivri, & Filiz, 2017), "Upoređivanje standardnih i novih testova ravnoteže kod rekreativnih alpinista i skijaša" (Cigrovski, Franjko, Rupcic, Bakovic & Matković, 2017), "Sistemsko mapiranje ženske odbojke na visokom nivou korišćenjem analize društvene mreže: slučaj pokrivanja napada, freeball i downball" , "Pouzdanost i važnost turske jezičke verzije testa strategije učinka" (Miço-oğulları, 2017), "Svjesnost studenata medicine o vezama između fizičke aktivnosti i zdravlja" (Mandic, Wilson, Clark-Grill & O'Neill, 2017), "Ispitivanje brzine plivanja kao metoda za razlikovanje profila mladih plivača" (Siljeg, Sindik & Leko, 2017), "Ispitivanje stavova studenata fizičkog vaspitanja -nastavnički smjer prema nastavničkoj profesiji" (Yildizer, Ozboke, Tascioglu, & Yilmaz, 2017), "Sveobuhvatno mapiranje vrhunskih odbojkaša kompjuterskih igrica kroz analizu socijalne mreže -Analiza serviranja, bočnog izlaza, bočne tranzicije i tranzicije" , "Zajedničko učenje korišćenjem ekranske tehnologije u fizičkom obrazovanju" (Luptáková & Antala, 2017) i "Funkcionalno-jača-nje: Pilot studija poboljšanja kontrole ravnoteže kod starijih u zajednicama" (Josephson & Williams, 2017).…”
Section: Picture 3 Kolaž Naslovnih Stranica (2015-2017)unclassified